A decade of the Commonwealth, 1955-1964 - Robinson, Kenneth; Hamilton, William Baskerville; Goodwin, Craufurd D. W. (Durham, N.C., Published for the Duke University Commonwealth-Studies Center [by] Duke University Press, 1966)
This volume is a product of a conference held at the Villa Serbelloni, Bellagio, Italy, June 29 through July 4, 1964 jointly arranged by the institute of Commonwealth Studies of the University of London and Duke University Commonwealth Studies Center. Participants represented seven Commonwealth countries and the United States
Bibliographical footnotes.
rpm 21/01/2019
Loans
Keywords: Commonwealth of Nations; Commonwealth countries